Disputas y significados del habitar en las localidades de San Mayol, Aparicio y Vásquez (provincia de Buenos Aires) en el marco del despoblamiento rural : 2004-2018 - Lopez Binaghi, Facundo (2022)
The loss of population and the possible disappearance of rural towns are depopulation processes that have been repeated throughout history in different parts of the world, this being a common reality in societies under capitalist development processes in agriculture. The productive model of the beginning of the last century, based on the export of agricultural primary products and with access to land for a certain part of the mainly migrant population, led to the rural towns of Buenos Aires having a significant development during the first half of the century XX. However, since the 1940s, the rural population has not only lost relative participation, but has also been reduced in absolute terms. In this context, peoples are also losing commercial and productive functions, social and educational services, leaving the infrastructures obsolete and empty of any function. At the rate that the population decreases, the remainder ages, the nuclei of sociability decline and it approaches the possibility of disappearing. This thesis seeks to reflect on the right to roots of those who inhabit these small towns, taking the habitat approach beyond the large urban conglomerates. It also seeks to contribute to a field of study that is still under construction, referring to rural towns and the development of the provincial territory.